Studi Evaluasi Pengelolaan Limbah B3 di Galangan PT. X - Bunga Ervina Rahma Berliana Putri; Muhammad Faisal Fadhil (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The shipyard of PT. X generates a huge amount of hazardous trash from ship repair activities, such as sandblasting waste, spent oil, used paint cans, and cleaning cloths. The purpose of this study is to classify and appraise B3 waste management operations, as well as to evaluate their execution. Data were gathered from observations, measurements, and interviews with the person in charge of Hazardous Waste Storage at the shipyard of PT. X. This study uses four stages in its implementation method, namely data collection, data processing and analysis, withdrawal, and provision of recommendations. Then the data will be compared with the applicable regulations. The average percentage of scoring was 73.375% with the achievement of